A CLINICAL STUDY TO EVALUATE THE EFFECT OF SARVANGA UDVARTANA FOLLOWED BY VIRECHANA KARMA AS ROOKSHA POORVAKA SHODHANA IN AMAVATA W.S.R TO RHEUMATOID ARTHRITIS - Singhal, *Prerana Rai; M Goud, Kiran; S J, Lolashri; Kumar K N, Vinay (International Journal of Ayurveda and Pharma Research, 2017)
The change in the classification of Rheumatoid Arthritis under various headings over the past few decades gives an insight to the pathology that requires a deeper understanding. Considering the role of immune mediating cells, progressive involvement of multiple joints & other systems, reduction in functional capacity, no other group of diseases is responsible for greater loss of earnings. The incidence of Rheumatoid Arthritis increases between 25 and 55years of age, after which it plateaus until the age of 75 and then decreases.Ayurveda understands this disease on the lines of Ama formation, Agni mandhya in rasa vaha srotas primarily, which over time dysfunctions all the 3 Agni (Jatharagni, Dhatwagni, Bhootagni) resulting in Sthabdham kurute gatram. The mainstay of treatment in Rheumatoid Arthritis comprises the early use of Disease Modifying Anti Rheumatic Drugs & Corticosteroids for induction of remission. As Amavata is an Abhishyandha pradhana vyadhi, adopting any snigdha modality of treatment will cause complications, hence identifying the degree of Sama - Nirama avastha in Amavata, Rookshana is to be done prior to any Snigdha chikitsa. Hence, the aim of this study was to evaluate the effect of Rookshana before Virechana Karma in the management of Amavata / Rheumatoid Arthritis. In this present clinical trial conducted in Varsha rtu, 10 diagnosed patients of Amavata / Rheumatoid Arthritis were selected. Statistical analysis showed highly significant improvement p <0.001 in almost all subjective & objective parameters of Amavata.